2018
DOI: 10.1002/anie.201810950
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective Pd‐Catalyzed C‐TeCF3 Coupling of Aryl Iodides

Abstract: While the TeCF3 moiety features promising properties and potential in a range of applications, no direct synthetic method exists for its incorporation into aromatic scaffolds. This report features the first direct catalytic method for the formation of C(sp2)−TeCF3 bonds. The method relies on a Pd/Xantphos catalytic system and allows for the trifluoromethyltellurolation of aryl iodides. Our computational and experimental mechanistic analyses shed light on the privileged activity of Xantphos in this transformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Beyond diaryl ditelluride substrates, we became interested in the oxidative fluorination of aryl‐TeCF 3 compounds. Syntheses of aryl‐TeCF 3 compounds have been developed by Umemoto and Ishihara, and more recently in our laboratory and by Schönebeck . To our satisfaction, under TCICA/KF conditions, we were able to convert phenyl‐TeCF 3 to trans ‐phenyl‐TeF 4 CF 3 ( 13 ), obtaining the product in 80 % isolated yield as an oil (Table ).…”
Section: Methodsmentioning
confidence: 83%
“…Beyond diaryl ditelluride substrates, we became interested in the oxidative fluorination of aryl‐TeCF 3 compounds. Syntheses of aryl‐TeCF 3 compounds have been developed by Umemoto and Ishihara, and more recently in our laboratory and by Schönebeck . To our satisfaction, under TCICA/KF conditions, we were able to convert phenyl‐TeCF 3 to trans ‐phenyl‐TeF 4 CF 3 ( 13 ), obtaining the product in 80 % isolated yield as an oil (Table ).…”
Section: Methodsmentioning
confidence: 83%
“…Fine-tuning of the reaction conditions and ancillary ligand, P t -Bu 3 versus PCy 3 , induced Ar–Cl over Ar–OTf chemoselectivity in Suzuki–Miyaura and Stille reactions . In the same vein, while developing a catalytic C–TeCF 3 coupling, Sperger et al recently showed that C­(sp 2 )–I bonds were selectively functionalized over C­(sp 2 )–Br/Cl/OTf bonds when using Xantphos as ligand . Furthermore, spectacular advances have been made varying the “metal form”: Pd­(I) dimers and cationic Pd trimers have been found to enable chemoselective C–C and C–X couplings with activation of C–I over C–Br bonds and C–Br over C–OTf/C–Cl bonds …”
Section: Introductionmentioning
confidence: 99%
“…Recently, tetramethylammonium trifluoromethylthiolate has been explored as a stable SCF 3 source, and it has been used in a large number of synthetic transformations. Other members in the chalcogenide series including tetramethyl­ammonium trifluoro­methylselenide ,, and trifluoro­methyltelluride have also been explored and utilized synthetically. , We previously reported the synthesis of heptafluoro­propoxide, nonafluorobutoxide, and nonafluoroisobutoxide from the reaction of perfluoroalkyl methyl ethers with tertiary amines . In an effort to address existing limitations with trifluoromethoxide reagents noted above, we were intrigued to investigate the corresponding reaction of trifluoromethyl methyl ether (CF 3 OCH 3 ; HFE-143a), a relatively safe and inexpensive gas that is used as a refrigerant or foam-blowing agent and a replacement for chlorofluorocarbons.…”
mentioning
confidence: 99%